Strength–ductility synergy at ambient and cryogenic temperatures via Cu-precipitation-tuned stacking fault energy in a Fe–Cr–Ni–Mn–Mo–Cu alloy - Sung, Min Young; Jang, Tae Jin; Lee, Hahun; Lee, Gunjick; Nam, Seungjin; Park, Gyumin; Zhang, Siyuan; Kim, Se-Ho; Sohn, Seok Su (Elsevier BV, 2026)
Achieving a favorable balance of strength and ductility at cryogenic temperatures requires concurrent control of yield strength and deformation mechanisms. Conventional carbide-based strengthening in Fe-based alloys can improve strength and modify deformation behavior, but often induces strain localization due to the non-shearable nature of carbides. Here, we show that nanoscale Cu precipitation in a designed Fe66Cr14Ni12Mn2Mo1Cu5 alloy simultaneously enhances strength and tailors stacking-fault energy (SFE) to activate multiple deformation modes. The coherent Cu precipitates with an average radius of ∼3 nm and a volume fraction of ∼5% contribute ∼190 MPa to yield strength through a shearing mechanism. The depletion of matrix Cu reduces the SFE from 23.3 mJ m−2 in the solutionized alloy to 15.6 mJ m−2, enabling deformation twinning at ambient temperature and promoting an earlier onset of γ→α′ martensitic transformation at 77 K. Consequently, the present alloy achieves a tensile strength of 1.43 GPa with ∼70% elongation at 77 K, corresponding to a strength–ductility product exceeding 10 GPa%. These findings establish precipitation engineering with shearable Cu precipitates as an effective strategy for simultaneously enhancing strength and controlling deformation pathways in cryogenic structural alloys.